2021
DOI: 10.1596/1813-9450-9787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Jamaica Early Childhood Stimulation Intervention on Labor Market Outcomes at Age 31

Abstract: We report the labor market effects of the Jamaica Early Childhood Stimulation intervention at age 31. The study is a small-sample randomized early childhood education stimulation intervention targeting stunted children living in the poor neighborhoods of Kingston, Jamaica. Implemented in 1987-1989, treatment consisted of a two-year home-based intervention designed to improve nutrition and the quality of mother-child interactions to foster cognitive, language and psycho-social skills. The original sample is 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Evidence from the famous Jamaican intervention on the impact of early childhood stimulation interventions for children from economically disadvantaged families has shown significant improvement in school performance and income gained at later stages of life (Gertler et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the famous Jamaican intervention on the impact of early childhood stimulation interventions for children from economically disadvantaged families has shown significant improvement in school performance and income gained at later stages of life (Gertler et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the intervention has been measured through randomized control trials which have shown benefits to child development and parenting outcomes ( 4 , 9 , 14–21 ). Substantial long-term benefits to cognition, education, mental health and income up to age 30 years have also been demonstrated ( 22 , 23 ).…”
Section: The Reach Up Early Childhood Parenting Programmentioning
confidence: 99%
“…Doing so, we obtain an IRR of 19.6%. Alternatively, we can use estimates from the 20 and 30-year follow-ups of the Jamaica early childhood stimulation trial, where Gertler et al (2014Gertler et al ( , 2021 find that the short-run gains for the treated children in cognition (0.91 SD) and language (0.59 SD) translate to 25% and 37% higher earnings at age 22 and 31 years, respectively. Hence the estimate we use to monetize a 1 SD gain in cognitive skills, 9% (at age 21 years, and assuming no growth in earnings thereafter), is likely a lower bound for low-income settings.…”
Section: Cost-benefit Analysismentioning
confidence: 99%